Ingestion and killing of Listeria monocytogenes by blood and milk phagocytes from mastitic and normal cattle. - Czuprynski, C J (1989)
Human listeriosis resulting from consumption of listeria-contaminated dairy products is emerging as a significant public health concern. There is a need to understand better the processes involved in the pathogenesis of Listeria monocytogenes-induced bovine mastitis. In the present report, we describe the results of the in vitro interaction of L. monocytogenes with bovine blood and milk leukocytes. Induction of an experimental L. monocytogenes mastitis resulted in a rapid and dramatic increase in neutrophils in the milk of infected cows. Blood neutrophils and mononuclear cells and milk leukocytes from listeria-infected and uninfected cows readily ingested L. monocytogenes in the presence of serum opsonins. These leukocytes also killed a portion of the ingested listeriae. Ingestion of listeriae evoked a vigorous chemiluminescence response by blood neutrophils and a relatively weak response by blood mononuclear cells. Ingestion, killing, and chemiluminescence by milk leukocytes were directly related to the percentage of neutrophils that were present. Blood neutrophils from healthy donor cattle ingested and killed L. monocytogenes when leukocyte-depleted milk and whey from mastitic cows were the sole sources of opsonins, although fewer listeriae were ingested than when normal bovine serum was present. These results indicate that bovine blood and milk phagocytes, like blood and inflammatory phagocytes from other mammalian species, can ingest and kill L. monocytogenes in vitro.